Relevansi Bahasa Daerah Terhadap Identitas Batak Karo di Desa Kutalimbaru - Azzahra, Aisya; Aulia, Lisa; Azzahra, Salsabila; Andini, Sri Wahyu; Wulandari, Tanya Chynta (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research investigates how regional languages, specifically the Karo language, influence the formation and preservation of Karo Batak ethnic identity in Kutalimbaru Village, Deli Serdang Regency, North Sumatra. Data were collected through participatory observation and in-depth interviews with informants from various generations within the Karo community. This data collection method uses a descriptive qualitative approach. The research results show that the Karo language is still used in daily life, especially within families and in traditional activities. However, due to the dominance of the Indonesian language, especially among teenagers, the Karo language is starting to change. Changes in the ethnic identity of the younger generation are indicated by the phenomenon of code-switching between Karo and Indonesian. However, the Karo language is still regarded as a marker of identity and respect for ancestors, and it remains an important symbol in traditional ceremonies and social interactions. External factors such as globalization, formal education, and migration pose significant challenges, while internal factors like the role of parents, religious institutions, and traditional leaders play a crucial role in language preservation. This research emphasizes that the preservation of the Karo language is crucial for maintaining the cultural identity of the Karo Batak amidst the ongoing social and cultural shifts.